Mechanisms of antibiotics inhibiting bacterial RNA polymerase. (15th January 2019) - Mosaei, Hamed; Harbottle, John
Abstract : Transcription, the first phase of gene expression, is performed by the multi-subunit RNA polymerase (RNAP). Bacterial RNAP is a validated target for clinical antibiotics. Many natural and synthetic compounds are now known to target RNAP, inhibiting various stages of the transcription cycle. However, very few RNAP inhibitors are used clinically. A detailed knowledge of inhibitors and their mechanisms of action (MOA) is vital for the future development of efficacious antibiotics. Moreover, inhibitors of RNAP are often useful tools with which to dissect RNAP function. Here, we review the MOA of antimicrobial transcription inhibitors.